My Browser is not a Billboard: Experimental Evidence on Ad-blocking Adoption and Users' Acquisition of Information - Niklas Fourberg; Serpil Tas; Lukas Wiewiorra (International Telecommunications Society (ITS), 2022)
Ad-avoidance technologies such as ad-blocking devices in browsers have become mainstream tools in recent years and escaped their role as niche applications that are only for the technically savvy. While technical impacts of those tools are well researched, their effects on actual consumer behavior is not. In an experimental setting this study provides first evidence on the effect of ad-blocking on users' ability to acquire information in the form of an online reading task. We find that ad-blocking leads to more effort being exerted and increases social welfare by reducing inefficient searching. Additionally, ad-blocking induces users' visit duration on websites to be more elastic in the experienced intensity of advertisements, making the competitive environment among publishers more intense.
Keywords: L82; L86; M37; C91; 330; Ad-blocking; consumer behavior; lab experiment; online advertising; welfare; privacy